Stress Analysis of Thoracolumbosacral Orthosis (TLSO) for Scoliosis deformity and its Effects on Gait Cycle - Kadhim, Fahad Mohanad; Ahmed, Sara I. (Al-Nahrain Journal for Engineering Sciences, 2019)
This work involved two major parts: the first one is the experimental part which included treatment of scoliosis deformity by manufacturing thoracolumbosacral orthosis, measuring the cobb angle of deformity, measuring the gait cycle data and walk path for both legs and suggesting a composite material to improve the mechanical properties of the orthosis and finally the interface pressure between trunk and orthosis is measured for twelve points covering of the total TLSO surface area by using f-socket devise. The second part of this study is the numerical simulation part during which the stresses are calculated using Ansys software for calculating stresses due to interface pressure loading boundary condition. The result shows no deference in gait cycle phases but the clear difference noted in walking path due to deviate center of mass, maximum pressure recorded left thoracic region with 900KPa due to correct spinal deformity while the minimum pressure recorded at right chest with l40KPa because of it is tissue region and Maximum value of stress was recorded at the left thoracic region with 2.81MPa due to Maximum interface pressure at this point.